Are We Speaking the Same Language? Finding Theoretical Coherence and Precision in "Mindfulness-Based Mechanisms" in Chronic Pain. Issue 11 (12th January 2017) - Harrison, Anthony M.; Scott, Whitney; Johns, Louise C.; Morris, Eric M.J.; McCracken, Lance M.
Abstract: Objective: Over the past 50 years, the field of chronic pain has witnessed an evolution of psychological approaches with some notable success. Some of this evolution has included "mindfulness-based interventions" (MBIs), now regarded as having encouraging partial support for their effectiveness. However, several theoretical challenges remain that may inhibit the progress of MBIs. These challenges include a lack of clarity surrounding the mindfulness construct itself, the proliferation of purported underlying mechanisms arising from different theories, and limited evidence for the mechanisms through which MBIs work. The current conceptual review provides a critique of existing theoretical models of mindfulness that have been applied to understanding and treating chronic pain. Design: A conceptual narrative review was conducted. Setting: Treatment programs for people with chronic pain. Patients: Individuals with any type of chronic pain. Interventions: MBIs for chronic pain. Outcome Measures: Mindfulness-based mechanisms explored in relation to several domains of functioning. Results and Conclusions: Based on this assessment, a summary of available evidence for a particular contextual behavioral theory of "mindfulness"—psychological flexibility—is outlined. Findings show the need for further integration of existing mindfulness constructs to better guide development and evaluation of mindfulness-based treatment methods in the future.